Analysis of the effect of diesel-essential oil fuel mixture on the performance, noise, vibration of diesel engines - Susilo, Sugeng Hadi; Listiyono, Listiyono; Khambali, Khambali (Eastern-European Journal of Enterprise Technologies, 2022)
The increasing demand for diesel fuel causes high levels of air pollution, noise, and vibration. Therefore, we need a mixture of materials that can reduce the environmental effect with low vibration. The purpose of this study was to investigate the effect of a diesel-essential oil mixture on a diesel engine, related to engine performance, noise, and vibration. The research was conducted using a 402 CC Dongfeng diesel engine, a mixture of diesel and essential oils with a percentage of 5 %, 10 %, 15 %, 20 %, engine speed of 1,300 rpm, 1,500 rpm, 1,700 rpm, 1,900 rpm. The noise intensity test uses a sound level meter at 30–130 dBA with a frequency between 20–20,000 Hz. To test the density of smoke, a smoke tester was used. Meanwhile, to measure the rotational speed of the engine, a DT 2234L type tachometer was used. A digital stopwatch was used to measure the processing time with an accuracy of up to 0.01 s. Besides that, a strain gauge was also used to detect vibrations. A measuring cup was used to measure the volume of the mixture of fuel and essential oils. The results showed that in the B10 mixture at 1,300 rpm engine speed, the largest fuel consumption time was 155 s. While the smallest fuel consumption time is found at 1,900 engine speed, which is 106 s. The lowest percentage of exhaust emissions is in the B20 mixture, which is 56.8 %. While the largest percentage of exhaust emissions is in B0 with a value of 79.8 %. The lowest noise value is in the B10 mixture at 1,300 rpm engine speed, which is 105.7 dB. While the highest noise value is at 1,900 engine speed, which is 112.3 dB. The lowest vibration is in the B10 mixture with an engine speed of 1,300 rpm, which is 975.7 Hz. While the highest noise value is in the B10 mixture with 1,900 engine speed, which is 989.8 Hz.